2022
DOI: 10.3389/fsurg.2022.825239
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radiation Therapy on Outcomes of Artificial Urinary Sphincter: A Systematic Review and Meta-Analysis

Abstract: BackgroundTo compare incontinence rates and complications in patients receiving artificial urinary sphincter (AUS) with or without radiotherapy (RT).MethodsPubMed, Embase, ScienceDirect, CENTRAL, and Google Scholar databases were searched for studies comparing outcomes of AUS between patients with and without RT. Search limits were from 1st January 2002 to 15th September 2021.ResultsEighteen studies were included. Meta-analysis revealed statistically significant reduced odds of the absence of incontinence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Minimal clinically important differences are reported to be 2.5 in ICIQ-SF, 17 3 in IPSS, 18 0.5 in IPSS-QOL, 18 and 3 in OABSS. 19 Theoretically, the differences over minimal clinically importance between the groups will be observed in Although several researchers reported that RT was associated with a high complication rate after AUS implantation, 9,11,13 In conclusion, longitudinal deterioration in LUTS that improved immediately after AUS implantation was observed in patients with a history of pelvic RT, unlike in patients without a history of pelvic RT whose LUTS (other than UI) did not deteriorate longitudinally after initial improvement. The deteriorating LUTS after AUS implantation in patients receiving RT might be attributed to impaired storage function by pelvic RT.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Minimal clinically important differences are reported to be 2.5 in ICIQ-SF, 17 3 in IPSS, 18 0.5 in IPSS-QOL, 18 and 3 in OABSS. 19 Theoretically, the differences over minimal clinically importance between the groups will be observed in Although several researchers reported that RT was associated with a high complication rate after AUS implantation, 9,11,13 In conclusion, longitudinal deterioration in LUTS that improved immediately after AUS implantation was observed in patients with a history of pelvic RT, unlike in patients without a history of pelvic RT whose LUTS (other than UI) did not deteriorate longitudinally after initial improvement. The deteriorating LUTS after AUS implantation in patients receiving RT might be attributed to impaired storage function by pelvic RT.…”
Section: Discussionmentioning
confidence: 91%
“…[5][6][7][8] In contrast, other studies reported that a history of RT was associated with significantly worse outcomes, including continent status and complications after AUS implantation. [9][10][11][12][13] To date, there have been no studies investigating the impact of a history of pelvic RT on LUTS other than UI after AUS implantation.…”
Section: Introductionmentioning
confidence: 99%
“…This may portend an increased risk for device erosion or urethral atrophy. A recent meta-analysis of 18 studies on AUS outcomes indicated that radiation therapy not only reduces the odds of achieving complete continence after AUS placement, but also significantly increases the risk for revision surgeries, urethral erosions and subsequently, explantations (31). Recent multicenter studies echo the same conclusions.…”
Section: Discussionmentioning
confidence: 90%
“…However, there is no clinical study exclusively conducted on patients with PPI treated with radiation, and this will be really welcome in order to stratify risk factors of failure in these patients. Some professionals consider the option of ATOMS in this population more than other types of slings because radiotherapy is considered a contraindication for retrobulbar slings [ 39 ], and there is some controversy about whether it worsens the results of AUSs [ 40 , 41 ].…”
Section: Atoms Resultsmentioning
confidence: 99%